Deconjugated Bile Salts Produced by Extracellular Bile-Salt Hydrolase-Like Activities from the Probiotic Lactobacillus johnsonii La1 Inhibit Giardia duodenalis In vitro Growth - Travers, Marie-Agnès; Sow, Cissé; Zirah, Séverine; Deregnaucourt, Christiane; Chaouch, Soraya; Queiroz, Rayner M. L.; Charneau, Sébastien; Allain, Thibault; Florent, Isabelle; Grellier, Philippe (Frontiers in Microbiology, 2016)
Giardiasis, currently considered a neglected disease, is caused by the intestinal protozoan parasite Giardia duodenalis and is widely spread in human as well as domestic and wild animals. The lack of appropriate medications and the spread of resistant parasite strains urgently call for the development of novel therapeutic strategies. Host microbiota or certain probiotic strains have the capacity to provide some protection against giardiasis. By combining biological and biochemical approaches, we have been able to decipher a molecular mechanism used by the probiotic strain Lactobacillus johnsonii La1 to prevent Giardia growth in vitro. We provide evidence that the supernatant of this strain contains active principle(s) not directly toxic to Giardia but able to convert non-toxic components of bile into components highly toxic to Giardia. By using bile acid profiling, these components were identified as deconjugated bile-salts. A bacterial bile-salt-hydrolase of commercial origin was able to mimic the properties of the supernatant. Mass spectrometric analysis of the bacterial supernatant identified two of the three bile-salt-hydrolases encoded in the genome of this probiotic strain. These observations document a possible mechanism by which L. johnsonii La1, by secreting or releasing BSH-like activity(ies) in the vicinity of replicating Giardia in an environment where bile is present and abundant, can fight this parasite. This discovery has both fundamental and applied outcomes to fight giardiasis, based on local delivery of deconjugated bile salts, enzyme deconjugation of bile components, or natural or recombinant probiotic strains that secrete or release such deconjugating activities in a compartment where both bile salts and Giardia are present.